A dynamic account of verb doubling cleft construction in Chinese. (January 2017) - Yang, Xiaolong; Wu, Yicheng
Abstract: In Mandarin Chinese, there exists a particular type of construction called "verb doubling cleft construction" (henceforth VDCC) like Chi, (wo) shi chi-guo le, buguo … (literally 'As for eating, I have indeed eaten, but…'), where the two verbs act as a topic and a verum focus, respectively. Cheng and Vicente (2013) claim that VDCC shares the same internal syntax with regular clefts, based on Cheng (2008)'s proposal that (i) the copula shi 'be' takes a small clause, and (ii) the two verbs stand in an A-bar movement relation. In this paper, we present a dynamic account of VDCC within the framework of Dynamic Syntax (Kempson et al., 2001; Cann et al., 2005). Under a parsing-based analysis, the first verb is shown to be an elliptical expression which denotes some event established in previous discourse, and the second verb is also an elliptical expression which needs to recover its content based on the interpretation of the first verb in topic position. Highlights: A dynamic account of Chinese verb doubling construction is provided. The first verb is analyzed as an event-denoting elliptical expression. The second verb is also an elliptical expression whose interpretation relies on the first verb.